Outcomes with nondose‐dense chemotherapy for Ewing sarcoma: A practical approach for the developing world. Issue 11 (24th July 2020) - Parambil, Badira Cheriyalinkal; Vora, Tushar; Sankaran, Hari; Prasad, Maya; Bakshi, Asish; Puri, Ajay; Gulia, Ashish; Qureshi, Sajid; Laskar, Siddhartha; Khanna, Nehal; Shah, Sneha; Ramadwar, Mukta; et al.
Abstract: Background: The current multidisciplinary approach in the treatment of Ewing sarcoma has improved cure rates, with contemporary dose‐dense chemotherapy attaining 5‐year event‐free survival (EFS) of 73% in localized cases. Dose‐intense and dose‐dense chemotherapy is difficult in the majority of resource‐limited settings with limited access to optimal supportive care. We report on patients with Ewing sarcoma treated on EFT‐2001, a nondose‐dense chemotherapy protocol. Procedure: A retrospective analysis was conducted of patients (<15 years) with Ewing sarcoma treated with curative intent during January 2013‐June 2017 with an institutional ethics committee‐approved nondose‐dense protocol (EFT‐2001). Local therapy was planned after 9‐12 weeks of chemotherapy with metastatic sites addressed with radiotherapy. The study assessed outcomes and prognostic factors. Results: We analysed 200 patients with M:F ratio of 1.27:1 and metastases in 41 patients (20.5%). At a median follow up of 41.5 months (range 4.5‐81.8 months), respective 3‐year EFS and overall survival (OS) of the whole cohort is 65.3% (95% confidence interval [CI]: 58.1‐71.7%) and 79.3% (95% CI: 72.8‐84.5%); for localized and metastatic cohort, 70.9% (95% CI: 62.9‐77.5%) and 82.8% (95% CI: 75.7‐89.0%); and for metastatic cohort, 42.8% (95% CI: 28.0‐58.6%) and 65.3% (95% CI: 47.7‐78.3%). Presence of residual disease (morphologic/metabolic) on positron emission tomography‐computed tomography scan done 3 months post definitive radiotherapy (hazard ratio [HR] 7.92 [95% CI: 3.46‐18.14]) and delay in any form of local control >4 months (HR 3.42 [95% CI: 1.32‐8.89]) affected outcomes. Nonrelapse mortality during treatment was 6.5%, mainly due to cardiomyopathy (3.0%) and bacterial sepsis (1.5%). Cardiotoxicity was seen in 11.5% of patients. Conclusions: Nondose‐dense chemotherapy provides good outcomes with manageable toxicities in a multidisciplinary treatment approach, while reducing cumulative drug exposures in the developing world where dose‐intense or dose‐dense chemotherapy could potentially increase toxicity, and hence seems a feasible approach in resource‐limited settings. Presence of any residual disease post definitive radiotherapy or delay in local control portends poor outcome.